Land use and ecosystems services value changes and ecological land management in coastal Jiangsu, China. (October 2016) - Chuai, Xiaowei; Huang, Xianjin; Wu, Changyan; Li, Jianbao; Lu, Qinli; Qi, Xinxian; Zhang, Mei; Zuo, Tianhui; Lu, Junyu
Abstract: A high density of anthropogenic activities and land use changes can significantly affect both the ecosystem services value (ESV) and ecosystem functions. Using land use images, crop yield data, empirical data related to ESV, a linear programming model and a CLUE-S model, our study analyzed the impact of land use changes on ESV, suggested an optimized land use structure for 2020 to maximize ESV and simulated the spatial distribution of ESV in coastal Jiangsu, China. The results showed that both built-up land and water area increased markedly between the 1980s and 2010, whereas all other types of land use decreased, especially for cropland and grassland. Land transitions showed relatively concentrated distributions near coastline areas and dispersed distributions in inland areas. Between the 1980s and 2010, land use changes resulted in a decrease of 43.20 million US.a −1 ESV that was primarily caused by the transition from cropland to built-up land, wetland to grassland and built-up land, and water area to cropland and built-up land. A proposed optimized land use structure would result in an increase of 435.20 million US.a −1 without considering any expansion of the area, ESV in 2020 compared to that in 2010 might demonstrate an effective method for land managers to adopt. The main type of transfer for ESV loss involves the future occupation of wetlands and croplands by built-up land, and the transformation of cropland into water area will greatly offset this loss. There continues to be a high probability that the coastline area will experience land transfer by 2020, coastline is the key region that needs strict land use management or control. Highlights: We optimized land use structure in 2020 to max ESV and simulated its spatial distribution. Expansion of built-up land contributed the most to loss ESV. Land use changed more obviously in the near coastline areas. The optimized land use structure presented effective to max ESV. Coastline region has high probability for land use change in 2020.